Private Information and Optimal Infant Industry Protection - B. Ravikumar; Raymond G. Riezman; Yuzhe Zhang (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study infant industry protection using a dynamic model in which the industry's cost is initially higher than that of foreign competitors. The industry can stochastically lower its cost via learning by doing. Whether the industry has transitioned to low cost is private information. We use a mechanism-design approach to induce the industry to reveal its true cost. We show that (i) the optimal protection, measured by infant industry output, declines over time and is less than that under public information, (ii) the optimal protection policy is time consistent under public information but not under private information, (iii) the optimal protection policy can be implemented with minimal information requirements, and (iv) a government with a limited budget can use a simple approach to choose which industries to protect.
Keywords: F10; F13; O25; D82; 330; protection; infant industry; private information; mechanism design; time consistency